Annual Plan 1998-99 State Planning Commission - Planning Commission (Planning Commission, 1998)
The outlay for the Ninth Five Year Plan (1997-2002) was finalised at Rs.25,000 crores. The Plan aims at a growth of 7% per annum. the outlay for 1997-98 Annual Plan, the first year of the Ninth Plan, was approved at Rs.4,009 crores and according to the revised estimates, the plan performance is expected to be Rs.4,010 crores. the Plan outlays in the succeeding Annual Plans need to be stepped up. During the Annual Plan discussion held on 5.8.1998, between the Hon’ble Chief Minister and Deputy Chairman of the Union Planning Commission, the plan outlay has been finalised at Rs.4500 Crores. Analysis of Tamil Nadu’s Economy 1997-98: State Income: 2. With 5.74 percent growth, the Net State Domestic Product in 1997-98 (AE) in real terms is expected to go up to Rs.18193.25 crores from Rs.17204.86 crores in 1996-97 (QE). the per capita income (at constant prices) of the State would increase from Rs.2918 in 1996-97 to Rs.3057 in 1997-98.
State Planning Commission Tamil Nadu